Cerebellar Development and Plasticity: Perspectives for Motor Coordination Strategies, for Motor Skills, and for Therapy - J. D. Swinny; J. J. L. van der Want; A. Gramsbergen (Neural Plasticity)
The role of the mammalian cerebellum ranges from motor coordination, sensory-motor integration, motor learning, and timing to nonmotor functions such as cognition. In terms of motor function, the development of the cerebellum is of particular interest because animal studies show that the development of the cerebellar cortical circuitry closely parallels motor coordination. Ultrastructural analysis of the morphological development of the cerebellar circuitry, coupled with the temporal and spatial identification of the neurochemical substrates expressed during development, will help to elucidate their roles in the establishment of the cerebellar circuitry and hence motor activity. Furthermore, the convenience of a number of naturally occurring mouse mutations has allowed a functional dissection of the various cellular elements that make up the cerebellar circuitry. This understanding will also help in the approach to possible therapies of pathologies arising during development because tile cerebellum is especially prone to such perturbation because of its late development.